Vascular endothelial growth factor gene 1154 G/A, 2578 C/A, 460 C/T, 936 C/T polymorphisms and association with recurrent pregnancy losses - Uncu, G.; Atalay, M. A.; Ozgoz, A.; Demir, B. C.; Samli, H. (Genetics and Molecular Research, 2012)
Vascular endothelial growth factor (VEGF) regulates endothelial cell proliferation, migration and differentiation. VEGF plays a critical role in angiogenesis during placenta formation. We investigated whether VEGF gene polymorphisms are associated with recurrent pregnancy loss. Thirty-eight women with recurrent pregnancy loss and 30 control women with live-born children were recruited from 2010 to 2011 in the region of Bursa, Turkey. VEGF gene polymorphisms were assessed with PCR-RFLP analysis of DNA samples obtained from leukocytes. DNA fragments were investigated by using appropriate primers. SNP scanning was performed using MnII, BgIII, BshI2361, Hsp92II restriction enzymes for 1154 G/A, 2578 C/A, 460 C/T, and 936 C/T polymorphisms, respectively. The frequencies of 2578 C/A, 460 C/T, 936 C/T polymorphisms were not significantly different between the controls and women with recurrent pregnancy loss. However, the prevalence of the 1154 G/A polymorphism A/A genotype was significantly higher in the recurrent pregnancy loss group (23.7 vs 3.4%). One of the four common polymorphisms of the VEGF gene was found to be more frequent in women with recurrent pregnancy loss. It is possible that disruption of VEGF function and placental angiogenesis can contribute to pregnancy loss in women with recurrent pregnancy loss.
Keywords: Adult; Vascular Endothelial Growth Factor A; Abortion, Habitual; Base Sequence; Sequence Analysis, DNA; Middle Aged; Polymorphism, Single Nucleotide; Young Adult; Pregnancy; Case-Control Studies; Humans; Female; Genetic Association Studies; Polymorphism, Restriction Fragment Length; DNA Primers